Tailoring the Magnetic Properties of Cobalt Antidot Arrays by Varying the Pore Size and Degree of Disorder - Escrig-Murua, J; Palma-Solorza, J; Casagrande-Denardin, J; Briones, J (Institute of Physics Publishing, 2014)
Magnetic properties of Co antidot arrays with different hole sizes fabricated by a template-assisted method have been studied by means of first-order reversal curves (FORCs) and micromagnetic simulations. Hysteresis curves show a significant increase of the coercivity of the antidot arrays, as compared with their parent continuous film, which depends on the hole size introduced in the Co thin film. This effect is related to the reversibility of the magnetic domains during magnetization reversal, since due to the appearance of pores, domains may become trapped between them. On the other hand, micromagnetic simulations performed on a perfect hexagonal lattice, when compared with those made on our disordered system taken from the scanning microscope images, reveal that the presence of defects in the antidot lattice affects its magnetic properties. Finally, FORCs show that there is greater interaction attributed to domain-domain interaction. © 2014 IOP Publishing Ltd.